Pengaruh Budaya Organisasi dan Lingkungan Kerja Terhadap Kinerja Karyawan dengan Kepuasan Kerja Sebagai Variabel Intervening pada PT. Padang Distribusindo Raya DC Padang Aro - Hendri Gusma Hendra; Dori Mittra Candana; M. Afuan (Ebisnis Manajemen, 2024)
This study aims to test how much influence Organizational Culture and Work Environment have on Employee Performance with Job Satisfaction as an Intervening Variable at PT. Padang Distribusindo Raya DC Padang Aro. The population in this study was 40 respondents with a sample of the population, namely 40 employee respondents of PT. Padang Distribusindo Raya DC Padang Aro. The sampling method of the study was carried out by questionnaire and observation. The research sample technique used was the Saturated Sampling technique using Structur Equation Modeling (SEM) and Partial Least Square (PLS) by distributing questionnaires to 40 respondents. The results of the data analysis concluded that there was a significant influence of organizational culture on job satisfaction. There was a significant influence of the work environment on job satisfaction. There was a significant influence of organizational culture on employee performance. There was a positive insignificant influence of the work environment on employee performance. There was a significant influence of job satisfaction on employee performance. There was a significant influence of organizational culture on employee performance through job satisfaction. There was a positive insignificant influence of the work environment on employee performance through job satisfaction.